Infiltrating inflammatory cells: Profile and distribution in feline mammary carcinomas (Research, Society and Development, 2021)
Malignant mammary tumors have a relatively high number of infiltrating T lymphocytes. Currently, B lymphocytes infiltrated in tumors have been recognized as a potential marker in human breast cancer. The aim of this study was to relate prognostic factors of mammary tumors to the pattern of inflammatory infiltrate in cats. Protocols of 38 animals diagnosed with mammary tumor were analyzed and data on sex, age and race were obtained. The samples were evaluated for distribution, histological type, size, histological grade, lymph node metastasis, inflammatory cell distribution and intensity of inflammation. For immunohistochemical staining, anti-CD79a monoclonal antibody was used. There was a predominance of elderly and mixed breed cats. Tubular, solid and cribriform carcinomas were the most diagnosed. Grade III tumors smaller than 2.0 cm were frequent. The total inflammatory infiltrate was predominantly multifocal and of low count, regardless of the histological type, degree and size. Lymphocytes were the most frequent and low-count cells. CD79a immunostaining was observed in most neoplasms, showing that B lymphocytes and plasma cells are integral components of the inflammatory infiltrate of the tumor and of predominantly diffuse distribution. Positive CD79a cells showed significant differences in distribution (p = 0.038), in size (p = 0.045) and lymphatic invasion (p = 0.039). This is the first study to quantify inflammatory cells in the mammary tumor microenvironment of cats and reveals promising initial results. CD79a positive cells constitute a significant portion of the lymphocyte population in the tumor microenvironment and are part of the tumor-associated inflammatory response in feline breast carcinomas.